Diversity of Water Insects in Colo Dam, Sukoharjo Regency - Wahyuni, Tri; Wiharti, Tri; Nugroho, Anwari Adi (Jurnal Biologi Tropis, 2024)
Aquatic insects are among the most successful groups of macroinvertebrates in freshwater habitats. This condition is indicated by the composition, presence and wide distribution as well as the ability of insects to adapt to various types of freshwater habitats which are components of bottom water communities. The aim of this research was to determine the diversity index, species richness index and dominance index of aquatic insects in Colo Dam, Nguter District, Sukoharjo Regency. This research method is quantitative descriptive. Quantitative analysis includes measuring the Diversity Index (H'), Species Richness Index (R1) and Dominance Index (D). The results of research on water insects at Colo Dam found 27 species. The highest number of individuals is the Water Strider with 75 species, while the fewest species are Rhinocypha perforata with 16 species. The conclusion of this research is that the Diversity Index of 3.23 is considered moderate. The type of Wealth Index obtained at 3.67 is considered medium and the Dominance Index at 0.0416 is considered low. Recommendations for further research include adding a Biotic Index to see the quality of the waters in the Colo Dam. It is hoped that the results of this research can become a reference or further research.